Formation of Nascent Chemoautotrophic Carbon Fixation Systems under Different Redox Conditions of Fluid Degassing of the Early Earth - Marakushev , Sergey A.; Belonogova , Ol`ga V. (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 9, 2023)
In theories of the origin of life, the most reasonable is the concept of the primacy of autotrophic metabolism, in which carbon dioxide (CO2) is considered as the only source of carbon for the functioning of nascent metabolic pathways. The aim of this paper was to demonstrate that the origin and development of primary autotrophic metabolism on early Earth were influenced by the two different regimes of degassing of the Earth – reducing (predominance CH4) and oxidative (CO2). It follows from this that the ancestral carbon used in metabolism may have been derived from CH4 if the outflow of magma fluid to the surface of the Earth consisted mainly of methane. In such an environment, the primary autotrophic metabolic systems had to be methanotrophic. Due to the absence of molecular oxygen in the Archean conditions, this metabolism would have been anaerobic, i.e., oxidation of methane should have been carried out by inorganic high-potential electron acceptors. In light of the primacy and prevalence of CH4-dependent metabolism in hydrothermal systems of the ancient Earth, we propose a model of carbon fixation where the methane is fixed/transformed in a sequence of reactions in an autocatalytic methane-fumarate cycle. Nitrogen oxides are thermodynamically most favorable among possible oxidants of methane; however, even the activity of oxygen created by mineral buffers of iron in hydrothermal conditions is sufficient for methanotrophic acetogenesis. The Hadean - Archaean hydrothermal system model is considered in the form of a phase diagram, which demonstrates the area of redox and P, T conditions favorable for the formation and development of primary methanotrophic metabolism.